Impact of Right Coronary Artery Bypass Grafting on Development of Atrial Fibrillation in Coronary Artery Bypass Grafting Surgery: A Retrospective Study - Yilmaz, Seyhan; Aydin, Ertan; Zengin, Sabür; Yılmaz, Elvan Tekir; Çelik, Abdullah (Revista brasileira de cirurgia cardiovascular, 2025)
Previous studies suggest that the location of coronary artery disease cannot independently predict atrial fibrillation after coronary artery bypass grafting, but with little information, it has also been thought that simultaneous right coronary endarterectomy may cause this rhythm problem. In this study, we aimed to evaluate the effect of right coronary artery bypass grafting on early postoperative atrial fibrillation. Patients who underwent elective on-pump coronary artery bypass grafting operations in our hospital were included in the study, and patients who underwent a different open-heart surgery or those who had previously undergone open-heart surgery were not included. Patients included in the study were divided into Group 1 (patients who developed postoperative atrial fibrillation) and Group 2 (patients who did not develop postoperative atrial fibrillation) and compared in terms of right coronary artery bypass grafting and other follow-up parameters. The mean age of a total of 158 patients included in the study was determined as 63.25 ± 10.07 years (range 44 - 85 years), 120 were male, and 96% of them had hypertension. Postoperative atrial fibrillation developed in 43 patients, and right coronary artery bypass grafting was performed in 123 patients. We think that the frequency of postoperative atrial fibrillation development may be higher in cases where right coronary artery bypass grafting is performed, as it may play a role in processes related to the conduction system and right ventricular dysfunction, and multicenter studies with a large number of patients would be beneficial on this subject.